2023
DOI: 10.1002/art.42412
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Efferocytosis by Synovial Macrophages in Patients With Knee Osteoarthritis

Abstract: Objective. Osteoarthritis (OA) exposes all joint tissues to physiologic stresses, increasing the need to clear apoptotic cells from tissues, including the synovium. We undertook this study to assess the burden of apoptotic cells in synovial tissue in patients with late-stage knee OA and to investigate whether OA impairs the macrophage-mediated clearance of apoptotic cells via efferocytosis.Methods. Synovial tissue was collected from individuals with healthy knees and patients with late-stage knee OA during art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The resident-like A cluster that emerged after injury expressed Mrc1 (CD206), historically associated with an anti-inflammatory and reparative phenotype, and which has been shown to mediate collagen turnover 58, 59 . In addition their potentially beneficial role in regulating extracellular matrix, the resident-like A population also expressed Gas6 , which is required for efficient efferocytosis of apoptotic cells by synovial macrophages 60 – an important aspect of inflammatory resolution that goes awry in OA 16 . It is noteworthy that conventional “M1” and “M2” markers, such as Il1b , Tnf , Arg1 and Il10 , revealed no appreciable separation across our clusters, placing further impetus to move beyond the simplistic M1-M2 spectrum of macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resident-like A cluster that emerged after injury expressed Mrc1 (CD206), historically associated with an anti-inflammatory and reparative phenotype, and which has been shown to mediate collagen turnover 58, 59 . In addition their potentially beneficial role in regulating extracellular matrix, the resident-like A population also expressed Gas6 , which is required for efficient efferocytosis of apoptotic cells by synovial macrophages 60 – an important aspect of inflammatory resolution that goes awry in OA 16 . It is noteworthy that conventional “M1” and “M2” markers, such as Il1b , Tnf , Arg1 and Il10 , revealed no appreciable separation across our clusters, placing further impetus to move beyond the simplistic M1-M2 spectrum of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage ablation in mice by clodronate liposomes yielded generally favorable OA outcomes, including reduced osteophyte formation 13, 14 , however pharmacogenetic macrophage depletion using the MaFIA mouse resulted in systemic inflammation, exacerbated immune influx into the joint, with no attenuation of OA severity 15 . Indeed, synovial macrophages play critical physiological functions such as the timely clearance of apoptotic cells, which is impaired in OA 16 . In a model of inflammatory arthritis, Huang et al showed that resolution requires the suppression of pro-inflammatory, systemically-derived F4/80 hi MHC Class II + macrophages and that macrophages with a resident-like phenotype promote inflammatory resolution 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Synovial tissue was dissected from the entire knee as previously described [ 16 ], pooled from 3 or 4 animals per replicate, providing n=5 replicates per condition at 4 and 12 weeks after joint surgery. After rinsing in PBS, synovial cells were enzymatically dissociated as previously described [ 7 ]. CD11b+ cells (monocyte/macrophage) were sorted using magnetic-activated cell sorting separation columns (Miltenyi Biotec) and lysed with TRIzol (Fisher Scientific) for RNA isolation using the Direct-zol RNA MicroPrep Kit (Zymo Research).…”
Section: Methodsmentioning
confidence: 99%
“…It is characterized by multi-articular, symmetrical, and invasive inflammation of the small joints of the hand and foot, often accompanied by involvement of extra-articular organs and positive serum rheumatoid factors, which can ultimately lead to joint deformity and loss of function [ 45 ]. Although impaired efferocytosis and elevated AC levels have been observed in the synovial tissue of patients with osteoarthritis [ 46 ], comprehensive evaluations of efferocytosis within RA synovial tissue are lacking. Inflammatory cytokines, including IL-1β, IL-6, IL-8, and TNF-α, have important roles in the pathogenesis of RA.…”
Section: Associations Between Efferocytosis and Autoimmune Diseasesmentioning
confidence: 99%